(untitled) (Eurasian Research Bulletin, 2024)
There are numerous ways in which coronavirus infection can adversely affect the liver. One notable aspect is the virus’s use of the angiotensin-converting enzyme 2 (ACE-2) receptor to infiltrate cells, particularly cholangiocytes, indicating the liver as a potential target. Research from the 2002 SARS outbreak revealed liver abnormalities such as increased mitotic cells and hepatocyte damage, suggesting virus-induced apoptosis and liver injury. Early-stage SARS-CoV infections were associated with abnormal levels of cytokines and chemokines, notably elevated IL-1, IL-6, and IL-10, indicating a correlation between liver damage and inflammatory responses. Patients with chronic liver diseases exhibited higher cytokine levels, potentially exacerbating liver injury during coronavirus infection. Moreover, patients co-infected with hepatitis B or C viruses demonstrated increased hepatitis virus replication and resistance to liver injury reversal